Cracked tooth diagnosis and treatment: An alternative paradigm - Mamoun, John S.; Napoletano, Donato (European Journal of Dentistry, 2015)
This article reviews the diagnosis and treatment of cracked teeth, and explores common clinical examples of cracked teeth, such as cusp fractures, fractures into tooth furcations, and root fractures. This article provides alternative definitions of terms such as cracked teeth, complete and incomplete fractures and crack lines, and explores the scientific rationale for dental terminology commonly used to describe cracked teeth, such as cracked tooth syndrome, structural versus nonstructural cracks, and vertical, horizontal, and oblique fractures. The article explains the advantages of high magnification loupes (×6–8 or greater), or the surgical operating microscope, combined with co-axial or head-mounted illumination, when observing teeth for microscopic crack lines or enamel craze lines. The article explores what biomechanical factors help to facilitate the development of cracks in teeth, and under what circumstances a full coverage crown may be indicated for preventing further propagation of a fracture plane. Articles on cracked tooth phenomena were located via a PubMed search using a variety of keywords, and via selective hand-searching of citations contained within located articles.
Keywords: Crack propagation; cracked tooth syndrome; microscopes; tooth fractures